2015
DOI: 10.7189/jogh.05.020416
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for respiratory syncytial virus associated with acute lower respiratory infection in children under five years: Systematic review and meta–analysis

Abstract: BackgroundRespiratory syncytial virus (RSV) is the most common pathogen identified in young children with acute lower respiratory infection (ALRI) as well as an important cause of hospital admission. The high incidence of RSV infection and its potential severe outcome make it important to identify and prioritise children who are at higher risk of developing RSV–associated ALRI. We aimed to identify risk factors for RSV–associated ALRI in young children.MethodsWe carried out a systematic literature review acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
222
10
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(288 citation statements)
references
References 36 publications
20
222
10
9
Order By: Relevance
“…ETS has been found to increase the risk of severe RSV disease as measured by hospitalization and hypoxia in both infants and children (adjusted OR 2.2–3.8) [46]. A recent systematic review and meta-analysis identifying risk factors for RSV-associated LRTI in children reported maternal smoking to be one of the most important risk factors (OR 1.36, 95% CI 1.24–1.50) [47] (Table 4). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ETS has been found to increase the risk of severe RSV disease as measured by hospitalization and hypoxia in both infants and children (adjusted OR 2.2–3.8) [46]. A recent systematic review and meta-analysis identifying risk factors for RSV-associated LRTI in children reported maternal smoking to be one of the most important risk factors (OR 1.36, 95% CI 1.24–1.50) [47] (Table 4). …”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis identifying risk factors for RSV-associated LRTI in children reported maternal smoking to be one of the most important risk factors (OR 1.36, 95% CI 1.24–1.50) [47] (Table 4). …”
Section: Resultsmentioning
confidence: 99%
“…HIV is an important risk factor for severe RSV infections, especially in high-burden settings [86]. HIV-infected children are older and may develop RSV outside of the seasonal peaks.…”
Section: Tuberculosismentioning
confidence: 99%
“…[20,21] Consistent with other studies, RSV occurred in young infants with the peak incidence under 6 months. [22] Maternal immunisation against RSV during late pregnancy may therefore be an attractive novel strategy to prevent disease in young infants. [23] In addition, B. pertussis occurred in young infants, and mostly before completion of the primary series of three immunisations; in turn, immunisation of pregnant women with B. pertussis may also be an effective strategy to prevent this burden.…”
Section: Guest Editorialmentioning
confidence: 99%